EXAMINING THE IMPACT OF ECONOMIC GROWTH, POVERTY AND UNEMPLOYMENT ON INFLATION IN INDONESIA (2000-2019): EVIDENCE FROM ERROR CORRECTION MODEL - Rosdiana Sijabat (Jurnal Studi Pemerintahan, 2022)
The study examines the causal relationship of economic growth, poverty, unemployment, and inflation in Indonesia from 2000 to 2019. The data analyzed are sourced from World Bank Indicators from The World Bank. The variables studied were inflation as the dependent variable and economic growth, the level of poverty, and the unemployment rate, inflation, as an independent variable. The results of the Augmented Dicky-Fuller test show that there is a unit root problem because all variables are not stationary at the level, so it is continued by doing first differencing, and stationary data is found in the first difference or I(1). Using the Vector Error Correction Model (VECM), this study found a significant long-term relationship between inflation (INF), economic growth (GP), the poverty rate (POV), and the unemployment rate (UNEMP). Meanwhile, in the short term, economic growth and poverty rates have a significant adverse effect on inflation. The results have important policy implications, specifically, the urgency of government policies and interventions to encourage the expansion of economic activities that promote economic growth and eradicate poverty.